Enhancing Inclusive Practices in Workplaces: Perspectives from People with Disabilities - Widadsyah, Muhammad Azhar (Indonesian Journal of Disability Studies, 2024)
Many persons with disabilities (PWDs) participated in working environment in Indonesia who participate in the working environment in Indonesia often report mistreatment and discrimination that they receive within the workplace. Despite many organizations and researchers purposefully seeking to improve inclusion within the workplace, challenges emerge due to the lack of understanding about the perspectives of PWDs regarding the adjustments and improvements needed to achieve better inclusivity. Semi-structured interviews were conducted with seven PWDs from various industries and disability conditions. The aim was to gain an in-depth understanding of PWDs perspectives about inclusion practices in their respective workplaces. In principle, the results show that the discriminative assumptions about PWDs can be considered as a one-dimensional view and do not provide a chance for PWDs to prove otherwise. However, these discriminatory views influence the treatment of PWDs on multiple levels. Furthermore, the results also highlighted issues experienced by PWDs in the recruitment, selection, social integration, and performance management phases. Improvements to address the issues highlighted by PWDs are focused on adjustment on recruitment procedures, improvement on accessible facilities and adjustments, providing accessible information system, improve employee capabilities through training and development, as well as provide mechanism to enable job flexibility. Furthermore, these steps need organizational value and diversity enhancement, and could be helped by collaboration with third party organization. The findings might help companies to enhance inclusion in their workplaces through effective ways and directly addressing the issues experienced by PWDs.